Topiramate Versus Propranolol in the Prophylaxis of Migraine in Bangladeshi Population - Tayeb, Muhammad; Md Hasanuzzaman, -; Karim, Abul Mansur Md Rezaul; Sanaullah, Mohammad; Islam, Md Ashraful (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background : Migraine is primary headache disorder characterized by recurring attacks of pain and associated symptoms. The management modality is still unsatisfactory due to poor understanding of its cause and pathogenesis. To assess the efficacy and safety of low dose Topiramate vs Propranolol in migraine prophylaxis. Materials and methods : A randomized clinical trial including 130 patients with frequent migraine headache >5 attacks per month was performed in the out patients Department of Medicine and Neurology, CMCH for a period of 12 weeks. The patients were randomly divided into two treatment groups – treated by Topiramate 50mg/day and Propranolol 80mg/day respectively. Topiramate started with 25mg/day for 7 days then increased up to 50mg/day in two divided dose. Propranolol started with 40mg/day for 7 days then increased up to 80mg/day in two divided dose. The patients were assessed at 0, 8 and 12 weeks of the study. Results: The Topiramate group showed a reduction in the mean (±SD) of frequency of migraine attack from 6.95(±2.88) to 1.75(±1.08) episode per month, headache days per month from 7.62(±4.14) to 1.83(±1.10), intensity of headache per attack from 8.98(±1.05) to 6.10(±2.50) based on VAS scale, duration of headache per episode from 11.56(±9.16) to 5.40(±2.97) per hour and MIDAS score from 16.19(±3.91) to 8.14(±3.93). In patient treated with Propranolol, the mean (±SD) of monthly frequency of migraine attack declined from 7.09(±2.87) to 1.92(±0.98) episode per month, headache days per month from 8.17(±4.52) to 1.86(±o.83), intensity of headache per attack from 8.47(±1.10) to 6.03(±2.05) based on VAS scale, duration of headache per episode from 11.16(±8.08) to 5.97(±3.45), MIDAS score from 15.48(±3.55) to7.77(±3.49). Pre- and post-treatment values were significantly different for individual groups but no significant difference observed between groups. Conclusion: This study demonstrated that both low dose Topiramate and propranolol could significantly reduce migraine frequency, intensity and duration. Chatt Maa Shi Hosp Med Coll J; Vol.18 (2); July 2019; Page 12-17